EFFECT OF INTERNAL MAMMARY ARTERY HARVESTING WITH AND WITHOUT PLEUROTOMY ON RESPIRATORY COMPLICATIONS IN PATIENTS UNDERGOING CORONARY ARTERY BYPASS GRAFTING - Iqbal, Javed; Khan, Faridullah; Abbasi, Saleem; Abid, Abdul Rehman (Journal of Ayub Medical College Abbottabad, 2016)
Background: Respiratory problems are one of the major issues faced by cardiovascular surgeons, which increase morbidity and mortality among patients undergoing coronary artery bypass grafting (CABG). It is possible to harvest the left internal mammary artery (LIMA) without opening the left pleura; however this cannot be reliably achieved in all cases due to intimate anatomical relationship. This study was designed to evaluate the effect of internal mammary artery harvesting with and without pleurotomy on respiratory complications in patients undergoing coronary artery bypass grafting. Methods: In this observational study 90 patients who underwent coronary artery bypass surgery were included by review of records. Patients were stratified into two groups according to surgical procedures, i.e., Internal Mammary artery harvesting with pleurotomy; (WP Group) (n=45) and with extra pleural harvesting technique; (EP Group) (n=45). Inclusion criteria were elective coronary artery bypass grafting, age over 18 years, willingness to be randomly assigned, provision of informed consent. Exclusion criteria were chronic obstructive pulmonary disease (COPD) or skeletal abnormalities that caused pulmonary restriction. Only the first 30 days postoperative outcome was studied. Data was analysed using SPSS version 21. Results: The demographic characteristics in terms of age and gender were comparable in study groups. The preoperative clinical presentation and medical history were also found similar. The hospital stay was significantly longer in WP Group than EP Group patients (7.2 vs 6.1 days, p<0.005). Moreover, post-operative morbidity was more prevalent in WP group 10 (22.2%) than EP Group 3 (66%) (p<0.03). In WP Group more respiratory complications were observed; 2 (4.4%) patients had dry cough and atelectasis, 1 (2.2%) patient experienced pleural effusion, 3 (6.6%) had bronchospasm while 1 (2.2%) patient each had sternal dehiscence and bleeding, however, these did not differ significantly among study groups. Conclusion: Respiratory complications were more frequent in patients undergoing Internal Mammary artery harvesting with pleurotomy compared to those managed extra pleural harvesting. Keywords; Coronary Artery Bypass Grafting, Left Internal Mammary Artery, pleurotomy, extra pleural, respiratory complications